2015
DOI: 10.1001/jamapsychiatry.2015.0276
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Neuroanatomic Specificity of Episodic Memory Dysfunction in Schizophrenia

Abstract: IMPORTANCE Individuals with schizophrenia can encode item-specific information to support familiarity-based recognition but are disproportionately impaired encoding interitem relationships (relational encoding) and recollecting information. The Relational and Item-Specific Encoding (RiSE) paradigm has been used to disentangle these encoding and retrieval processes, which may depend on specific medial temporal lobe (MTL) and prefrontal cortex (PFC) subregions. Functional magnetic resonance (fMRI) imaging during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 31 publications
6
53
1
Order By: Relevance
“…As in previous studies of chronic patients (Ragland et al 2012a, 2012b, 2015), discriminability following both item and relational encoding was impaired for FE participants. The FE group also showed pronounced recollection deficits following item as well as relational encoding, the same pattern previously noted for patients with long-term illness (Ragland et al 2012a, 2012b, 2015). One area of difference was familiarity-based retrieval.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As in previous studies of chronic patients (Ragland et al 2012a, 2012b, 2015), discriminability following both item and relational encoding was impaired for FE participants. The FE group also showed pronounced recollection deficits following item as well as relational encoding, the same pattern previously noted for patients with long-term illness (Ragland et al 2012a, 2012b, 2015). One area of difference was familiarity-based retrieval.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to CHR participants, we examined patients during a first episode of psychosis (FE). Most previous studies (e.g., Achim & LePage, 2003; Ragland et al, 2015; Williams et al 2010) examined more chronically ill patients. By investigating FE participants we aim to discover if the encoding and retrieval deficits associated with chronic schizophrenia are also apparent early in the illness.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the lack of greater activation for the CON versus SCZ group is unlikely to be an artifact, as greater activation in CON than SCZ was seen during working and relational memory paradigms that were completed during the same scanning session (Ragland et al, in Press; Sheffield et al, 2015). However, a fuller exploration of the effects of higher level visual processing on JOVI performance was precluded by the lack of sufficient data for analysis of activity in bilateral IFG pars triangularis and parietal angular gyrus, as described in Footnote 1.…”
Section: 0 Discussionmentioning
confidence: 99%
“…The Relational and Item-Specific Encoding task (RISE) was developed to directly address memory after these different types of encoding processes [5,6]. This computer-based paradigm manipulates encoding by having participants actively utilize 2 methods for analyzing visual pictured stimuli of real-world entities: an item-specific and a relational method.…”
Section: Introductionmentioning
confidence: 99%
“…After 30 min, recognition memory for all of the items or pairs of items is assessed and d′ scores for item-encoded or relationally encoded stimuli are derived. In a series of studies, the test was shown to have acceptable test-retest reliability, to consistently activate medial temporal lobe (MTL) subregions in fMRI studies, and to yield profiles of performance in schizophrenia characterized by disproportionate impairments in memory after relational encoding as well as hippocampal and dorsolateral prefrontal activation failures [5,6]. …”
Section: Introductionmentioning
confidence: 99%